Cellular mechanisms underlying extraordinary sulfide tolerance in a crustacean holobiont from hydrothermal vents. Issue 1990 (11th January 2023) - Chou, Pei-Hsuan; Hu, Marian Y.; Guh, Ying-Jey; Wu, Guan-Chung; Yang, Shan-Hua; Tandon, Kshitij; Shao, Yi-Ta; Lin, Li-Yih; Chen, Chi; Tseng, Kuang-Yu; Wang, Min-Chen; Zhang, Cheng-Mao; et al.
Abstract : The shallow-water hydrothermal vent system of Kueishan Island has been described as one of the world's most acidic and sulfide-rich marine habitats. The only recorded metazoan species living in the direct vicinity of the vents is Xenograpsus testudinatus, a brachyuran crab endemic to marine sulfide-rich vent systems. Despite the toxicity of hydrogen sulfide, X. testudinatus occupies an ecological niche in a sulfide-rich habitat, with the underlying detoxification mechanism remaining unknown. Using laboratory and field-based experiments, we characterized the gills of X. testudinatus that are the major site of sulfide detoxification. Here sulfide is oxidized to thiosulfate or bound to hypotaurine to generate the less toxic thiotaurine. Biochemical and molecular analyses demonstrated that the accumulation of thiosulfate and hypotaurine is mediated by the sodium-independent sulfate anion transporter (SLC26A11) and taurine transporter (Taut), which are expressed in gill epithelia. Histological and metagenomic analyses of gill tissues demonstrated a distinct bacterial signature dominated by Epsilonproteobacteria . Our results suggest that thiotaurine synthesized in gills is used by sulfide-oxidizing endo-symbiotic bacteria, creating an effective sulfide-buffering system. This work identified physiological mechanisms involving host-microbe interactions that support life of a metazoan in one of the most extreme environments on our planet.